Preparation and capacitor optimization of MnO2/AC using I-optimal coordinate exchange model - Tilahun Temesgen; Eneyew Tilahun Bekele; Bedasa Abdisa Gonfa; C.R. Ravikumar; Lemma Teshome Tufa; Syed Khasim; Dereje Tsegaye; H.C. Ananda Murthy; Yilkal Dessie (Results in Chemistry)
In this study, to improve the poor electrical conductivity and low stability performance of MnO2, which affects its charge storage performance, nanostructured MnO2 decorated water hyacinth (Eichhornia crassipes) stem-based activated carbon (AC) composites were synthesized using simple mixing of AC in KMnO4 solution by employing three factors with three level of designed model. The I-optimal Coordinate Exchange model was designed to optimize MnO2/AC composites for high-performance capacitors (supercapacitors). For these optimized responses, KMnO4 concentration, water hyacinth leaf extract, and mass loading effects of AC observed at 0.68 M, 19.6 mL, and 0.47 g, respectively, were found to be selected as optimized values. At these optimized values, a maximum of 161.18 F g−1 specific capacitance was achieved. To address the correlation, significance, and acceptability of the model design, the regression coefficient (R2), adjusted (R2), adequate precision, and p-values were found to be 0.9973, 0.9892, 27.904, and 0.0081, respectively. This indicates the strong correlation between the actual and predicted values, and the proposed model is statistically significant. The structural, optical, surface topography, and electrochemical properties of the optimized MnO2/AC composites were characterized by XRD, BET, UV–Vis, FTIR, SEM-EDX, TEM, HRTEM, SAED, CV, EIS, and GCD techniques. The final optimized composites exhibited an excellent performance with a high specific capacitance of 153.12 F g−1 at the current density of 2 A g−1 after 2000 cycles with an excellent cycling performance of ≈ 95 % capacitive retention in 6 M KOH electrolyte.